CHATBOT WHATSAPP SEBAGAI MEDIA EDUKASI DAN PENDAMPINGAN REMAJA DALAM MENDUKUNG IMPLEMENTASI KEBIJAKAN KESEHATAN BERBASIS TEKNOLOGI - Dwi Nur Siti Marchamah; Agus Sudrajat; Ghina Putri Nurul Aini; Sania Aly (Jurnal Abdi Masyarakat, 2026)
Adolescents face various health challenges, such as unbalanced diets, poor nutritional monitoring, and limited access to ongoing education. This community service project focuses on strengthening health literacy through the use of digital technology relevant to adolescents' lives. The objective of the activity is to improve knowledge and healthy living behaviors through WhatsApp chatbot-based education and mentoring. The method used was a participatory approach for 47 students through interactive counseling, Body Mass Index (BMI) measurements, dietary guidance, and the use of the chatbot as a reminder and consultation medium. Evaluation was conducted using pre- and post-tests. The results showed an increase in understanding and awareness of balanced nutrition and BMI monitoring, with an increase in positive responses of around 18%, as well as more active participation due to easier and more personalized access to information.